Spontaneous Reductıon Occurrıng Durıng Natural Sleep ın Anterıor Shoulder Dıslocatıon Cases: A Serıes of Four Cases - Akar, Bedrettin; Sukur, Erhan; Balioglu, Mehmet; Ozturkmen, Yusuf; Ugur, Fatih (Open Medical Publishing, 2025)
In this study, the authors report that in four cases of anterior shoulder dislocation resulting from trauma, where reduction attempts under emergency conditions failed due to muscle spasm caused by severe pain, the state of natural sleep induced by analgesic and sedative medications administered in the observation room helped relax the muscles around the shoulder joint. This relaxation prevented spasm and allowed spontaneous reduction of the shoulder joint to occur within a few hours, without the need for anesthetic intervention.